The Routledge handbook of critical finance studies - Borch, Christian; Wosnitzer, Robert (New York, NY : Routledge, 2021)
"The term 'critical finance studies' remains largely unfocused and undefined. Against this backdrop, the key rationales of The Routledge Handbook to Critical Finance Studies are to provide a coherent notion of this emergent field and to demonstrate its analytical usefulness across a wide range of central aspects of contemporary finance"--
OCLC-licensed vendor bibliographic record.
Keywords: Finance; Critical theory; BUSINESS & ECONOMICS / Finance; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Accounting / Financial